FAKTOR-FAKTOR YANG DOMINAN MEMPENGARUHI KEPUASAN PASIEN RAWAT INAP PADA RUMAH SAKIT UMUM BINA KASIH MEDAN - Lintresa, Laura; Silalahi, Esli; Purba, Saut (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the dominant factors affecting the satisfaction of BPJS inpatients. The study population was 1732 BPJS patients who were hospitalized in June-July 2019. The research sample consisted of 70 patients. The data collection techniques used were documentation and questionnaires. The data obtained were analyzed by factor analysis. Based on the results of the study, it was concluded that the most dominant factors affecting the satisfaction of inpatients at the Bina Kasih General Hospital in Medan were performance factors, additional features, endurance, reliability, responsiveness, assurance, empathy, infrastructure, situation description, social environment, controlling emotions. , price levels, payment terms, service fees. Of the fourteen indicators, it can be seen that the service cost factor must be considered by the hospital because this factor is the complaint of patients at the Bina Kasih General Hospital in Medan.